AKTUALISASI NILAI PENDIDIKAN AKHLAK PADA ANAK USIA DINI - Siti Qosidah (Al'Adalah, 2016)
Education is a process which helps the growth of human’s personality in positive direction. In other words, education is consciously guiding and helping the students based on physical and spiritual development in maturity. Toddler education is to form the quality of Indonesian children in order to be able to grow and develop in accordance with the level of development. Thus, they are going to be ready in entering their basic education and face their life in the future optimally. Moreover, this education is going to help the children in reaching their readiness learning in the school.